(untitled) (Journal of Nepal Geological Society, 2004)
The Asian Arsenic Crisis has expanded into the headwaters of the Ganges River, now including the plains (Terai) of Nepal. This study seeks a non-invasive predictive tool to estimate groundwater arsenic concentration prior to drilling, enabling "arsenic avoidance" in contaminated areas. Detailed chemical studies indicate that in Himalayan-sourced aquifers arsenic is released by microbially-mediated redox reactions. Likely hydrogeological settings for oxidizing chemical conditions (immobile arsenic) should be more porous (higher in filtration rate for oxygenated waters) and contain fewer fine organic sediments (oxygen-consuming material). Both conditions should yield higher electrical resistivity, and such aquifer heterogeneity effects should be most prominent in head water regions such as Nepal. To test this approach, a series of vertical electrical resistivity soundings were made near Parasi, Nepal, constituting a profile extending 2 km across a known high-arsenic area. Correlation of the horizontal and vertical distribution of measured resistivity and ENPHO groundwater arsenic measurements demonstrated a distinct inverse relationship between these variables. Out of 240 arsenic sample points, 75% of those extracted from high resistivity zones (>100 ohm-m, inferred lower clay content) exhibited arsenic <150 ppb. Conversely, 7S% of samples from low resistivity zones exhibited arsenic >150 ppb. Given these preliminary results, the resistivity technique appears to hold great promise as a predictive tool for finding low-arsenic groundwater zones within contaminated areas, thereby allowing "well-switching" from highly toxic to new safe or more readily treatable wells. The method should be applicable in most circum- Himalayan high-arsenic areas.